If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -7) + 33 = -5(x + -5) + 17x + -28 Reorder the terms: 4(-7 + 2x) + 33 = -5(x + -5) + 17x + -28 (-7 * 4 + 2x * 4) + 33 = -5(x + -5) + 17x + -28 (-28 + 8x) + 33 = -5(x + -5) + 17x + -28 Reorder the terms: -28 + 33 + 8x = -5(x + -5) + 17x + -28 Combine like terms: -28 + 33 = 5 5 + 8x = -5(x + -5) + 17x + -28 Reorder the terms: 5 + 8x = -5(-5 + x) + 17x + -28 5 + 8x = (-5 * -5 + x * -5) + 17x + -28 5 + 8x = (25 + -5x) + 17x + -28 Reorder the terms: 5 + 8x = 25 + -28 + -5x + 17x Combine like terms: 25 + -28 = -3 5 + 8x = -3 + -5x + 17x Combine like terms: -5x + 17x = 12x 5 + 8x = -3 + 12x Solving 5 + 8x = -3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 5 + 8x + -12x = -3 + 12x + -12x Combine like terms: 8x + -12x = -4x 5 + -4x = -3 + 12x + -12x Combine like terms: 12x + -12x = 0 5 + -4x = -3 + 0 5 + -4x = -3 Add '-5' to each side of the equation. 5 + -5 + -4x = -3 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = -3 + -5 -4x = -3 + -5 Combine like terms: -3 + -5 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| -5(-2x+2)=-9x | | -7x-3y=-7 | | 6st+9t+10s-15= | | -32-7x=4(4x-8) | | -3.6-r=(-6r+0.6) | | 4+4x-x^2-x^3=0 | | 3x-15+x=180 | | -6-2(-9x-8)=-3 | | s=q+3/x | | .40c+4-.20c=-9 | | -23=-t | | b-4c+3a-c-9b-4a=0 | | 5(6x-5)+51=-6(x-7)+18x+2 | | -8x-9+5x=-9x+3 | | x+3=5x+2 | | 4.9t^2+2.14t+42=0 | | 5F-9C=120 | | 3/2*16*1/2 | | 7/2*16*-1/2 | | .5x-2.3=0.7 | | 3x+7x+4=2x-6 | | -21.15=m-6.33-6.7m | | 15/2*64*-1/2 | | -8a-b-(-6c)-2a-b-5c=0 | | x-3/10-8=3x+2 | | 6-2x+7-3x=12 | | 2*6*w+2*w*8+2*6*8=208 | | 9x-7=9(x-5) | | 15/2((64)-1/2) | | -2c=pm^2-n | | -(x+2)=-18-x | | X-5/3=5/4 |